Extended Tam: Actual Technological Determination And Its Impact On SMEs - Devi Febrianti; Mega Barokatul Fajri (Universitas Muhammadiyah Malang, 2022)
This study aims to examine and analyze the factors that can influence the actual use of technology in SMEs through the extended technology acceptance approach. The method used is PLS analysis with 299 respondents from all UMKM in east java. The results of this study show that basically when individuals have the attitude to accept the use of technology, it will indirectly increase public interest in using technology so that it can increase the effectiveness, individual performance, and quality of financial reports in a UMKM. However, the effectiveness of using technology can't affect the size of a UMKM, because based on the results of questionnaires and interviews with respondents that the size of the company as seen from the total turnover and assets can't be influenced by the use and intensity of technology. The new finding from this research is the actual use of technology is able to mediate between behavioral intentionin individual performance and the quality of MSME financial reports is very large.